Characteristics and Patterns of Deep Neck Infection in Dr. Mohammad Hoesin General Hospital Palembang 2020 - Yanti, Lisa Apri (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Intoduction: Deep neck infection is the accumulation of pus in the potential space and facial area in the deep neck. The incidence of deep neck space infections is 1/100.000 in adults and 2/100.000 in children. Risk factors such as age, oral hygiene, and comorbidities such as DM are predisposed factors in deep neck infection. Effective pus collection of specimens is essential, to obtain the organisms and determine the effective antibiotics. Purpose: The aim of this study was to describe the characteristics and bacterial patterns of abscess in Dr. Mohammad Hoesin General Hospital Palembang. Methods: This study was conducted retrospectively using medical records of patients who diagnosed deep neck infection in Dr. Mohammad Hoesin General Hospital Palembang during January to December 2020 who took pus collection and been checked in microbiology laboratory. Data recorded include gender, age, site, onset, risk factors, comorbidities, bacteria culture, antibiotic sensitivity, and complications. Results: Of the 36 patients, 23 (63.8%) were males, followed by 13 (36.1%) were female, and the age of 31-45 years old group were found in 13 subjects (36.1%). The onset was mostly found at 0-1 week as many as 19 subjects (52.7%). The highest complaints of dysphagia and odynophagia were found in 22 cases (26,2%), odontogenic factors were found in 35 cases (97,2%). Abscess location in multiple space were found in 17 cases (47,2%), while in single space there were 19 cases (52.7%), where the most location was in submandibular space in 7 cases. Diabetes was the most comorbid factors found in 6 subjects (50%). The most bacterial were Klebsiella pneumoniae in 4 cases (11.1%) and sensitive antibiotics including ciprofloxacin, meropenem, and tigecycline, in 6 cases (20%) respectively. And the most complication was mediastinitis in 6 cases (75%). Conclusion: Klebsiella pneumoniae is the most common found in deep neck infection with sensitive antibiotics including ciprofloxacin, meropenem, and tigecycline.